Physical activity and screen-based recreation: Prevalences and trends over time among adolescents and barriers to recommended engagement - Jongenelis, M.; Scully, M.; Morley, B.; Pratt, Steve; Slevin, T. (Elsevier BV, 2017)
© 2017 Elsevier Inc. Adolescence is a critical time for disengagement from physical activity making young people a priority group for interventions. To determine whether existing initiatives are working in this population segment and help inform future programs, the present study sought to (i) examine prevalences and trends in physical activity and screen-based recreation among Australian adolescents and (ii) identify the barriers to adolescents meeting recommended guidelines. Two cross-sectional representative samples of Western Australian secondary school students aged 12 to 17. years were surveyed in 2009-2010 (n = 1505) and 2012-2013 (n = 1406). Around a quarter (24%) of boys and just 9% of girls reported engaging in the recommended 60. min of physical activity per day in 2012-2013. A minority (13% of boys, 17% of girls) adhered to guidelines for time spent engaging in screen-based recreation (=. 2. h of electronic media use for entertainment). These findings were comparable to 2009-2010 prevalence levels. Multivariable logistic regression analyses conducted on data from the most recent wave found individual-level barriers to be significantly associated with lower odds of meeting physical activity guidelines in both boys (Adj. OR = 0.52, 95% CI = 0.38, 0.72) and girls (Adj. OR = 0.41, 95% CI = 0.25, 0.66). The consistently high proportion of adolescents not meeting physical activity recommendations over time suggests that current efforts to increase physical activity may be failing to have an impact on population-level trends in compliance. While initiatives to improve the built environment may reduce barriers at the environmental level, these initiatives risk having little impact on physical activity if individual level barriers remain unaddressed.